Fraud Detection in Village Fund Management in Mandailing Natal District - Arfidawati, Sri; Nurlaila, Nurlaila; Mailin, Mailin (Budapest International Research and Critics University, 2022)
This study aims to detect the extent of fraud in the management of village funds in Mandailing Natal Regency. Corruption is one type of fraud that often occurs in the village fund management sector. To overcome this, forensic audits and investigative audits are methods used to detect fraud. In practice, forensic audits and investigative audits require information and evidence. The information and evidence can be sourced from the Audit Team of the Inspectorate of Mandailing Natal Regency. This study aims to determine the effectiveness of forensic audits and investigative audits in detecting Village Fund Management fraud as a supporting factor. The research method used is descriptive qualitative with data collection techniques using informants through directly using interview and documentation techniques. Data analysis in this study used data from the District Inspectorate Office. Christmas Mandailing. Based on the resulting comprehensive conceptual framework, it can be concluded that forensic audits and investigative audits are effective methods of detecting fraud in village fund management in Mandailing Natal district. The researcher concluded that in the village financial management in Hutabargot District, fraud was detected from 14 villages in Hutabargot District in 2020. Lack of training and supervision of the village fund management process can lead to deviations that can be detrimental, training is carried out to improve the ability of the apparatus In managing village funds, this is very necessary for the creation of good village fund management and in accordance with established rules.